Workforce agility: how to management knowledge and innovation in a remote work environment - Dias, Á.; Patão, C.; Pereira, L.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Agile Systems and Management, 2023)
The current pandemic context has highlighted the importance of remote work in companies. Typically associated with management work, telework can also be applied to several other areas, in particular innovation. Through a quantitative study, by means of a questionnaire survey to a sample of 115 individuals, we analysed the causality relationship of the variables according to the conceptual model elaborated and tested using structural equations. Thus, the results confirm the importance knowledge management process in a teleworking environment, and how these constructs, individually and together, influence organisational innovation. It was also found the mediating effect on the stages of the knowledge management process (knowledge acquisition, exploration and sharing). Organisations that have a culture that favours communication and sharing, even in telework, and have innovative strategies to manage knowledge will see an impact of knowledge management on innovation of the way it relates to others.